2012
DOI: 10.1007/jhep07(2012)146
|View full text |Cite
|
Sign up to set email alerts
|

From Navier-Stokes to Einstein

Abstract: We show by explicit construction that for every solution of the incompressible Navier-Stokes equation in p + 1 dimensions, there is a uniquely associated "dual" solution of the vacuum Einstein equations in p + 2 dimensions. The dual geometry has an intrinsically flat timelike boundary segment Σ c whose extrinsic curvature is given by the stress tensor of the Navier-Stokes fluid. We consider a "near-horizon" limit in which Σ c becomes highly accelerated. The near-horizon expansion in gravity is shown to be math… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
338
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(361 citation statements)
references
References 51 publications
13
338
1
1
Order By: Relevance
“…We also find the following additional condition for α = d from the first subleading order of the third constraint equation above: 8) where (0) ∇ i is the covariant derivative associated to g (0) and where the indices are raised with g (0) . These four particular conditions will play an important role in the analysis that follows next.…”
Section: Holographic Stress Tensorsmentioning
confidence: 87%
See 1 more Smart Citation
“…We also find the following additional condition for α = d from the first subleading order of the third constraint equation above: 8) where (0) ∇ i is the covariant derivative associated to g (0) and where the indices are raised with g (0) . These four particular conditions will play an important role in the analysis that follows next.…”
Section: Holographic Stress Tensorsmentioning
confidence: 87%
“…-7]. A different recent attempt [8][9][10] focuses on subregions of some Ricci-flat spacetime bounded by timelike hypersurfaces and reconstructs the metric of such a region from data belonging to a relativistic fluid describing the hydrodynamic regime of some QFT on the timelike boundary.…”
Section: Introductionmentioning
confidence: 99%
“…According to the membrane paradigm [4], external observers will find that BH horizons behave like fluid membranes, endowed with a viscosity, conductivity, temperature, entropy, etc. Moreover, in certain circumstances there are formal mappings between solutions of general relativity and solutions of Navier-Stokes [5,6]. Fluids, however, lack strong uniqueness theorems and admit a rich structure of solutions.…”
Section: Jhep07(2014)045mentioning
confidence: 99%
“…[28]. Here the effective gravitational dynamics of the D3-brane subject to Dirichlet boundary conditions at an appropriate cutoff surface was considered along the lines of ideas introduced in the paper(s) [29,30]. It was directly shown that the fluid/gravity correspondence and the hydrodynamic effective theory are obtained as the two (most interesting) extremes where the cutoff surface is taken to be located in the near-horizon throat region and at spatial infinity, respectively.…”
Section: Jhep04(2015)171mentioning
confidence: 99%